2017
DOI: 10.4103/1735-3327.201136
|View full text |Cite
|
Sign up to set email alerts
|

Cervical lymphadenopathy: Unwinding the hidden truth

Abstract: Lymphadenopathy is a common clinical finding in a patient seeking oral health care. It may be in a localized, limited, or generalized form. Malignancies, infections, autoimmune disorders, iatrogenic, and other miscellaneous conditions are considered as the causes for cervical lymphadenopathy. Unexplained cervical lymphadenopathy is a cause of concern for physician and patient because sometimes it could be the manifestation of an underlying malignancy. However, a methodological approach to lymphadenopathy can d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…A majority of the patients (45, 90.00%) had unilateral Tuberculous Cervical Lymphadenopathy (TCL), particularly more involvement of right side of cervical region (29, 58.00%). Commonly involved lymph node group was level V (26, 52.00%) followed by level III (12,24.00%) and level VI (5, 10.00%) ( Table 3). The ESR was raised in 45 (90.00%) patients and it was more than 30mm in the first hour in most of the cases.…”
Section: Infective Lymphadenopathy Tuberculosis Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…A majority of the patients (45, 90.00%) had unilateral Tuberculous Cervical Lymphadenopathy (TCL), particularly more involvement of right side of cervical region (29, 58.00%). Commonly involved lymph node group was level V (26, 52.00%) followed by level III (12,24.00%) and level VI (5, 10.00%) ( Table 3). The ESR was raised in 45 (90.00%) patients and it was more than 30mm in the first hour in most of the cases.…”
Section: Infective Lymphadenopathy Tuberculosis Metastasismentioning
confidence: 99%
“…There are many causes of cervical lymphadenopathy like malignancies, infections, autoimmune disorders, iatrogenic and other miscellaneous conditions. 12 There are more chances of wrong clinical diagnosis in case of lymphadenopathy than any other diseases. The certain diagnosis can be made on the bases of histopathological examination of lymph node's biopsies.…”
Section: Introductionmentioning
confidence: 99%
“…Homogeneous uptake with SUV max value of about 10 is seen. Primary breast lymphoma staging is done according to the Ann Arbor staging system [6]. It is classified as stage 1 if the involvement is limited to the breast, stage 2 if there are more than 2 axillary lymph nodes at the same side with breast involvement, stage 3 if there is lymph node involvement on both sides, and stage 4 if there is an extra lymphatic area or organ involvement.…”
Section: Discussionmentioning
confidence: 99%
“…None other studies that measured lymphadenopathies location were found. The second location was cervical lymphadenopathies (9.8 %), which can be also affected in other processes such as immune maturation, infections of the respiratory tract, inflammatory reactivity to vaccines, dentition and further miscellaneous conditions [27]. The mentioned processes can stimulate lymphadenopathies in general.…”
Section: Discussionmentioning
confidence: 99%